STRATEGI PEMASARAN PRODUK TALANGAN UMRAH PADA BANK SUMUT SYARIAH CAPEM MARELAN RAYA - Restu Agung Syahputra; Muhammad Lathief Ilhamy Nasution (Jurnal Publikasi Manajemen Informatika, 2025)
. This research aims to analyze the marketing strategy of umrah financing products at Bank Sumut Syariah Capem Marelan Raya. The research method used is qualitative with a field study approach, through observation and interviews with the Bank Leader. The results showed that the Bank implements a combination of conventional and digital marketing strategies. Factors such as competition, public understanding, and economic conditions affect marketing effectiveness. Strategic recommendations include increasing education, product innovation, and service enhancement. This research provides insights into sharia marketing and effective strategies in the context of umrah financing products.